2016
DOI: 10.1017/s0025315416000217
|View full text |Cite
|
Sign up to set email alerts
|

Size, sex and reproductive biology of seven pelagic sharks in the eastern Arabian Sea

Abstract: Studies on reproduction in sharks are important for their management, since the attainment of sexual maturity has a substantial impact on their distribution, behaviour and biology. However, reproductive biology of large oceanic sharks is poorly studied in the Indian seas. In this study, the size structure, sex and maturity of pelagic thresher (Alopias pelagicus), bigeye thresher (A. superciliosus), oceanic whitetip shark (Carcharhinus longimanus), tiger shark (Galeocerdo cuvier), shortfin mako (Isurus oxyrinch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Additionally, the results of this study were slightly lower than the 2021 IOTC report on the status of blue sharks in the Indian Ocean, which showed a male sexual maturity length of 201 cmTL. Similar results were also reported in studies conducted by [ 10 , 28 ]. The length at sexual maturity for females was similar to the global average reported size [ 27 ] but higher than the 194 cmTL reported in the 2015 IOTC report on the status of blue sharks in the Indian Ocean and the study by [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the results of this study were slightly lower than the 2021 IOTC report on the status of blue sharks in the Indian Ocean, which showed a male sexual maturity length of 201 cmTL. Similar results were also reported in studies conducted by [ 10 , 28 ]. The length at sexual maturity for females was similar to the global average reported size [ 27 ] but higher than the 194 cmTL reported in the 2015 IOTC report on the status of blue sharks in the Indian Ocean and the study by [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several fishery dependent surveys in waters of the Arabian Sea have indicated that the abundance of both species has drastically declined (e.g. Varghese et al 2017). Furthermore, a regional Arabian Sea and adjacent waters IUCN Red List of Threatened Species assessment has evaluated them as Critically Endangered and Endangered, respectively, suggesting population declines between 50 and 80% over the past 50-60 years (Jabado et al 2017).…”
Section: Declining Catches and Sizesmentioning
confidence: 99%
“…A. pelagicus also exhibits an annual reproductive cycle [16]. Research conducted by Varghese et al [18] stated that A. pelagicus did not have a resting phase in its reproductive cycle.…”
Section: Growth Of a Pelagicusmentioning
confidence: 99%
“…The reproductive strategy of A. pelagicus is closely related to several parameters, thus are, reproductive strategy; size at birth, size-at-maturity, age-at-maturity, gestation period, reproductive cycle, and sex ratio in embryos [10, 16,18]. A study conducted by Varghese et al [18] showed that during the 9-month gestation period, A. pelagicus has a reproductive strategy of aplacental viviparity by embryonic oophagus. Oophagus means eating eggs, in this reproductive strategy additional nutrients are given to developing embryos in the form of unfertilized eggs.…”
Section: Reproduction Of a Pelagicusmentioning
confidence: 99%